Three new cave-dwelling Eukoenenia (Palpigradi: Eukoeneniidae) from limestone caves in Northern Minas Gerais state, Brazil - Souza, Maysa Fernanda Villela Rezende; Ferreira, Rodrigo Lopes (Zootaxa, 2020)
In this paper, we describe three new Eukoenenia species from specimens collected in limestone caves in the northern region of the Minas Gerais state, Brazil. These species present different degrees of adaptation to the subterranean habitat, with Eukoenenia magna sp. nov., with 6 blades on lateral organs and body ratios very close to other troglobitic species, being the most troglomorphic among them. This species is morphologically very similar to the Brazilian troglobites E. navi, E. eywa and E. neytiri. Eukoenenia lundi sp. nov. and Eukoenenia jequitai sp. nov. are probably closely related species due to their substantial morphological resemblance. These two species are closer to E. virgemdalapa among the Brazilian species described to date. We provide a table summarizing the main diagnostic characters of the three species herein described and those of the Brazilian congeners to facilitate morphological comparisons.